PERAN PROMOSI TERHADAP MINAT MASYARAKAT DALAM MEMILIH BANK SYARIAH - Julisman; Savriadi; Martius (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to find out and analyze promotions carried out by Islamic banks and the extent to which promotion influences consumer interest in choosing Islamic banks, especially in Mutiara view housing, Sekupang sub-district, Batam city. The method used in this study is a quantitative descriptive method with multiple linear regression analysis techniques. Promotional media used by Islamic Banking in this study are divided into 3, namely: television media, newspaper media and internet media. The results of the comparison of t count with t table with an error level of 5% and N as many as 120 get the result that variable X1 is known t count 2.812 > t table 1.657 meaning that partially there is a significant influence, between the variables of promotion through television media on public interest. Variable X2 is known t count 0.587 <t table 1.657 meaning that partially there is no significant effect, between the promotion variables through the newspaper media on public interest. As well as the X3 variable, it is known that t count is 3.210 > t table 1.657, meaning that partially there is a significant influence, between the promotion variables through internet media on public interest. While the level of promotion through television, newspapers and the internet simultaneously or jointly has an influence on the dependent variable, namely public interest, with F count 20.158 > F table 2.68 and a significance level of 0.000 <0.05. Thus it can be explained that the independent variables in the form of television promotion media, newspapers and the internet together have an influence on the dependent variable, namely the interest of the Mutiara View housing community